Frakeki. Friulian language literacy in preadolescent children - BURELLI, ALESSANDRA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2010)
Friulian schools are witnessing a gradual increase in the teaching of Friulian, a minority language native to this area of Europe. As well as providing an opportunity for educational and linguistic research, the activity presented in this paper was aimed at teaching Friulian writing skills to lower secondary school students (11 to 14 year olds), using blog-writing in order to develop linguistic and communicative expertise and especially graphemic and textual competence. The activity, involving six local schools, confirmed that the use of communication technology in minority language teaching can reinforce a student’s positive attitude towards the language, thus playing an important role towards the achievement of the educational aims. In addition, the analysis of the written texts produced by the children has shed light on Friulian morphosyntax as used by Friulian-speaking preadolescents, revealing the strategies that they employ as they learn to write in Friulian and progress in their educational route.